Industry‐Dominated Science Advisory Boards Are Perceived To Be Legitimate…But Only When They Recommend More Stringent Risk Management Policies. Issue 11 (16th June 2020) - Árvai, Joseph; Gray, Sara Goto; Raimi, Kaitlin T.; Wilson, Robyn; Drummond, Caitlin
Abstract: In 2017, the US Environmental Protection Agency (EPA) was criticized for two controversial directives that restricted the eligibility of academic scientists to serve on the agency's key science advisory boards (SABs). The EPA portrayed these directives as necessary to ensure the integrity of the SAB. Critics portrayed them as a tactic by the agency to advance a more industry‐friendly deregulatory agenda. With this backdrop, this research examined board composition and its effect on the perceived legitimacy of risk management recommendations by the SAB. In an experiment, we presented participants with hypothetical EPA SABs composed of different proportions of academic and industry scientists. We then asked participants to rate their satisfaction with, and the legitimacy of, these boards in light of their decisions in scenarios based on actual EPA SAB deliberations. Participants perceived higher levels of satisfaction and legitimacy when SABs made more stringent risk management recommendations. While SABs dominated by industry scientists were perceived to be more strongly motivated to protect business interests, we found no effect of board composition on perceptions of satisfaction and legitimacy. These results are consistent with prior research on decision quality that suggests people use normative outcomes as a heuristic for assessing the quality of deliberations. Moreover, these results suggest that members of the public are supportive of federal SABs regardless of their composition, but only if they take actions that are consistent with normative expectations.